APLIKASI MANAJEMEN KEUANGAN DAN AJUAN HAK CIPTA PROSES PRODUKSI PRODUK USAHA KECIL MENENGAH (UKM) ISNAINI CRAFT KABUPATEN SEMARANG - Korawijayanti, Lardin; Karyanti, Tutik Dwi; Ciptaningtias, Arum Febriyanti; Pradana, Bagas Putra (Politeknik Negeri Semarang, 2024)
Recording financial reports is an important aspect of a business activity. Financial reports are used as a presentation of financial information used by both internal and external parties for business activities. Accounting practices are a solution to problems that often occur in micro, small and medium enterprises (MSMEs), namely financial management problems. So far, UKM Isnaini Craft has not made regular financial records, let alone made financial reports. So far, SMEs still mix household finances with business finances. This situation often becomes a problem in the smooth production and marketing of the business. The second problem in the New Normal era, the government wants changes to SMEs to improve performance in the fields of finance, production, marketing and resources. In terms of marketing performance, UKM Isnaini Craft needs help in its efforts to achieve competitive advantage by increasing the number of products that obtain Copyright Certificates from the Ministry of Law and Human Rights. Protection of Intellectual Property Rights (IPR) for micro, small and medium enterprises (MSMEs) plays an important role in the era of globalization. Protection efforts are carried out through submitting registration for MSME products that meet the requirements to be granted IPR so that as a consequence the government will provide protection such as patents, copyrights, brands, industrial designs and trade secrets.So, Community Service (PMK) aims to provide an understanding of the importance of financial management for businesses. The technique for resolving the first problem is to provide assistance in making financial records and preparing financial reports. Meanwhile, in the second problem, UKM Isnaini Craft. Will help fund and apply for the acquisition of a Copyright Certificate for 1 Isnaini Craft UKM product to the Director General of Intellectual Property, Ministry of Law and Human Rights.